Evaluación de la interacción del consorcio microbiano Pseudomonas sp y Chlorella sp como estimuladores de crecimiento vegetal bajo condiciones in vitro en semillas de tomate (Solanum lycopersicum L.) - Cumbicos Sarango, Nayeli Valeria (2024)
Tomato is the most important crop in the Ecuadorian diet and national economy; however, it is susceptible to phosphorus (P) efficiencies in early stages due to its insoluble form. Phosphate- solubilizing bacteria (PSB) have been a profitable alternative and ecological in recent years, the objective of the present research is to evaluate the interaction of the bacteria and microalgae consortium (Pseudomonas - Chlorella) in the solubilization of phosphorus in tomato under in vitro conditions, due to their antecedents as beneficial organisms. This study was carried out in two phases, the first in the plant microbiology laboratory and the second in the germplasm bank of the La Argelia experimental farm through a CRD where the absorbance for the phosphate calibration curve was calculated and measured the level of stimulation in tomato seeds, the results showed that the strain 9B (SP9) corresponding to Pseudomona fluorescens has better levels of solubilization but these benefits are limited in its use with Chlorella, which proved to be an excellent germination biostimulant, finally it is concluded that the use of a microbial consortium as a pre-germination medium is favorable compared to synthetic stimulants despite reducing total germination.